2020
DOI: 10.1101/2020.08.27.270371
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide analysis ofcis-regulatory changes in the metabolic adaptation of cavefish

Abstract: Changes in cis-regulatory elements play important roles in adaptation and phenotypic evolution. However, their contribution to metabolic adaptation of organisms is less understood. Here we have utilized a unique vertebrate model, Astyanax mexicanus, different morphotypes of which survive in nutrient-rich surface and nutrient-deprived cave water to uncover gene regulatory networks in metabolic adaptation. We performed genome-wide epigenetic profiling in the liver tissue of one surface and two independently deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Finally, cholesteryl esters (Table S6), and cholesterol in some feeding states (Table S2), were less abundant in cave populations. Using a previously published gene expression dataset (33), we investigated factors that might influence levels of cholesteryl esters. Cholesteryl ester transfer protein (CETP), which transports cholesterol in / out of lipoproteins, is down-regulated in both Pachón and Tinaja compared to surface fish (Fig S6), suggesting a potential causal relationship between lower cholesteryl ester levels in cave populations and this important carrier protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, cholesteryl esters (Table S6), and cholesterol in some feeding states (Table S2), were less abundant in cave populations. Using a previously published gene expression dataset (33), we investigated factors that might influence levels of cholesteryl esters. Cholesteryl ester transfer protein (CETP), which transports cholesterol in / out of lipoproteins, is down-regulated in both Pachón and Tinaja compared to surface fish (Fig S6), suggesting a potential causal relationship between lower cholesteryl ester levels in cave populations and this important carrier protein.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published RNA-Seq data (33) of CETP () and HMGCRA/B ( / ) in cave / surface A. mexicanus . Values on the y–axis are gene expression data in terms of counts measured in liver tissue under normal feeding conditions.…”
Section: Fig S1mentioning
confidence: 99%
“…Previous studies have shown drastic metabolic differences in the metabolism of surface fish and cavefish (4,5,14). Most of the differences that have been documented affect glucose and fat metabolism pathways.…”
Section: Cfl Have Increased Glycolytic Capacitymentioning
confidence: 98%
“…Astyanax mexicanus has emerged as a powerful system to understand the genetic and physiological basis of metabolic adaptation to nutrient deprived habitats (2)(3)(4)(5)(6)(7)(8)(9)(10). The species comes in two morphotypes -the surface fish that live in lush, nutrient-rich rivers and the blind cavefish that dwell in dark and nutrient-poor caves in the Sierra de El Abra of northeast Mexico.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation